Qualidade de tabletes orodispersíveis contendo 2,5 mg de besilato de anlodipino manipulados em farmácias magistrais do Espírito Santo (Brasil) : Quality of orodispersible tablets containing 2.5 mg of amlodipine besylate compounded in magistral pharmacies at Espírito Santo (Brazil) (Revista Brasileira Multidisciplinar, 2024)
Orodispersible tablet (ODT) is a solid pharmaceutical dosage form, with small dimensions, that can be sweetened and flavored and disintegrates quickly in the oral cavity, releasing the active pharmaceutical ingredient (API) without the need to drink water. Given these advantages, ODT is configured as an alternative pharmaceutical dosage form for use by patients who have difficulty swallowing. The objective of the present work was to investigate the quality of ODTs containing amlodipine besylate, manipulated in three magistral pharmacies in Espírito Santo (ES, Brazil), in order to verify if the products meet the quality criteria required for this pharmaceutical dosage form. After purchasing the products through medical prescription, the quality attributes were evaluated according to pharmacopoeic and non-pharmacopoeic methods, namely: packaging and labeling, organoleptic characteristics, average weight, diameter, thickness, friability, residual moisture, disintegration time, and drug content. All samples failed one or more quality parameters provided for in RDC 67/2007 for unitary dosage forms containing APIs in concentrations below 5 mg. Two samples did not meet with the United States and European pharmacopoeial requirements for disintegration time. Such findings are critical since the lack of product quality can lead to therapeutic inefficiency and compromise the safety of the treatment. The unsatisfactory performance may be related to problems that occurred in the compounding procedures, suggesting that there must be the identification of critical points for the compounding of this pharmaceutical dosage form, favoring the monitoring of the magistral process based on quality indicators.
Keywords: Orodispersible tablet; Amlodipine besylate; Quality indicator; Monitoring of the magistral process